Using Telemedicine Strategy to Implementing Nutrition Management for Neonates After Congenital Heart Disease Surgery: A New Nutrition Management Strategy - Zhang, Qi-Liang; Lin, Wen-Hao; Lin, Shi-Hao; Cao, Hua; Chen, Qiang (Frontiers in Pediatrics, 2022)
Objective: The purpose of this study was to investigate the effect of remote nutrition management on promoting growth and development of neonates after congenital heart disease (CHD) surgery. Methods: This study retrospectively analyzed the clinical data of 32 neonates after CHD surgery who were received remote nutrition management from January 2021 and July 2021 in our hospital. The clinical data of 30 neonates after CHD surgery who were not received remote nutrition management from June 2020 to December 2020 was as control. The growth and development of the two groups were compared. Results: Three months after discharge, the weight, height and WAZ of the intervention group was significantly higher than those of the control group (P<0.05). The amount of milk of the intervention group were also significantly more than that of the control group, and more neonate in the intervention group added high-energy milk or breast milk fortifier than the intervention group (P<0.05). The parental care ability of the intervention group was significantly higher than that of the control group (P<0.05). The incidence of respiratory tract infection and readmission in the intervention group was significantly lower than that in the control group (P<0.05). Conclusion: As a new nutrition management strategy for neonates after CHD surgery, remote nutrition management can effectively improve the nutritional status of neonates and promote their growth and development.